2011
DOI: 10.1021/ja2102373
|View full text |Cite
|
Sign up to set email alerts
|

Completely N1-Selective Palladium-Catalyzed Arylation of Unsymmetric Imidazoles: Application to the Synthesis of Nilotinib

Abstract: The completely N1-selective Pd-catalyzed arylation of unsymmetric imidazoles with aryl halides and triflates is described. This study showed that imidazoles have a strong inhibitory effect on the in situ formation of catalytically-active Pd(0)-ligand complex. The efficacy of the N-arylation reaction was improved drastically by the use of pre-activated solution of Pd2(dba)3 and L1. From these findings it is clear that while imidazoles can prevent binding of L1 to the Pd, once the ligand is bound to the metal, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 67 publications
2
79
0
Order By: Relevance
“…Previously, the N-arylation of 4-methylimidazole and bromobenzene with Pd/ L1 gave N -arylated product 3a in 95% yield with complete N 1 -selectivity. 7 The same N-arylation reaction using Pd/ L3 showed similar progress and the N -arylated product was obtained in 96% yield with complete N 1 -selectivity. Similarly, almost identical yields (90% with L1 , 89% with L3 ) and N 2 -selectivity (N 2 :N 1 = 97:3 for both L1 and L3 ) were observed for the N-arylation of 1,2,3-triazole.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Previously, the N-arylation of 4-methylimidazole and bromobenzene with Pd/ L1 gave N -arylated product 3a in 95% yield with complete N 1 -selectivity. 7 The same N-arylation reaction using Pd/ L3 showed similar progress and the N -arylated product was obtained in 96% yield with complete N 1 -selectivity. Similarly, almost identical yields (90% with L1 , 89% with L3 ) and N 2 -selectivity (N 2 :N 1 = 97:3 for both L1 and L3 ) were observed for the N-arylation of 1,2,3-triazole.…”
mentioning
confidence: 74%
“…5 We recently demonstrated that the combination of Pd and L1 was the most effective catalyst system for the highly N 2 -selective arylation of 1,2,3-triazoles 6 and completely N 1 -selective arylation of unsymmetric imidazoles. 7 L1 is synthesized from 1,2,3,4-tetramethylbenzene via dibromination and then a one-pot biaryl phosphine synthesis protocol, which proceeds through a benzyne intermediate. 4,5 However, the high cost and limited availability of the 1,2,3,4-tetramethylbenzene 8 could potentially prevent the utilization of Pd/ L1 systems, as well as the future development of methods using L1 as a supporting ligand for various metals.…”
mentioning
confidence: 99%
“…Formation of the amide bond between benzoic acid 6 and anilines 5a–c was more difficult than expected. Common procedures such as EDCI or DCC coupling in DCM, DCE, or acetonitrile failed; HATU coupling in DMF was not successful either; deprotonation of the aniline using potassium tert -butoxide in THF, followed by treatment of the resulting anilide 13 with the methyl ester of 6 also failed. Eventually, conversion of 6 to the corresponding acyl chloride, using thionyl chloride in the polar aprotic solvent NMP, followed by addition of anilines 5a–c provided nilotinib analogues 2a–c .…”
mentioning
confidence: 99%
“…A variety of fundamental transformations, such as hydrogenation of multiple bonds, 7 cross-coupling reactions, 8 heteroatoms (N, O, S) arylations, 9 C-H bond functionalizations 10 and so on, 11 rely heavily on palladium species. Recently, much attention has been paid to the palladium-catalyzed cascade process for efficient synthesis of heterocycles.…”
Section: (C) Intermolecular O-alkylation Andmentioning
confidence: 99%